Onduo Song At The Pasir Pengaraian Communities, In The Perspective Of Manifest And Latent Functions - Arman, Idawati; Anwar, Armansyah; Fitriah, Laila; Pramudya, Andang (Perspektif Pendidikan dan Keguruan, 2023)
This study aims to reveal the function of onduo song in the Malay community at Pasir Pengaraian, Rokan Hulu, Riau Province. The research method used is a qualitative method, with field work steps. While the data collection technique is by conducting in-depth interviews, field observations and document analysis. From the research results, it was found that there are two functions of onduo song in society, namely manifest and latent functions. The manifest function is a function that is done on purpose. This is found when singing is functioned in the context of cultural events, such as the konduo ceremony. The next manifest function is also found in the form of artist creativity, both dance and music, which makes the onduo song the main material of the work. The latent function is found in the meaning that accompanies each stanza of onduo song which is sung, in which the entire lyrics of singing onduo, although with different themes, contain similar messages, namely messages for good. Of course, this message is intended for the child who is being rocked, but it is also for the audience to consume.